Surprised by Children: A Call to Pedagogical Possibilities - Hill, Anne (Canadian Journal of Education/Revue canadienne de l'éducation, 1994)
Teaching young children is an opportunity to live within a context of paradox and uncertainty. This paper describes a teacher-researcher’s experiences of surprise in daily practice. I suggest that experiences of surprise, of the paradoxically expected/unexpected, the familiar/unfamiliar, and the childlike/unchildlike are opportunities to develop and sustain reflective teaching practice. The experience of surprise is more than a prompt to reflection. It is itself an embodied reflection. Lived experience comes to language through the encounter of the body/mind, and we awaken to pedagogical possibilities. L’enseignement dispensé à de jeunes enfants est une occasion de vivre dans les paradoxes et les incertitudes. Dans cet article, l’auteure décrit les surprises de chercheurs-enseignants dans l’exercice de leurs fonctions au jour le jour. Elle avance que ces surprises, ces expé- riences du prévu/imprévu, du familier/non familier, des réactions enfantines/non enfan- tines, sont autant d’occasions de développer et de maintenir des pratiques pédagogiques réflexives. L’expérience de la surprise fait plus qu’inciter à la réflexion. Elle constitue en elle-même une réflexion incarnée. L’expérience vécue passe dans les mots à travers la rencontre du corps et de l’esprit et nous éveille à diverses possibilités pédagogiques.